Effects of Budget Planning, Control, Realization on Ad Hoc Performance: HR Competence Moderation - Muh Erwinsyah (Journal of State Economic Research, 2026)
This study evaluates the fiscal governance efficiency of adhoc electoral institutions in Indonesia following the recent national elections. Utilizing the new institutional economics framework, this research examines the impact of budget planning, control, and realization on organizational performance, alongside testing the moderation effect of human resource competence. Employing an econometric approach on 183 observational units within Banggai Regency, empirical estimations prove that planning is entirely insignificant due to centralized regulatory rigidity. Conversely, absolute allocative efficiency is purely driven by accelerated budget realization and effective layered monitoring, which successfully mitigates economic deadweight loss. Furthermore, individual operational capacity fundamentally fails to moderate performance outcomes because of the bureaucratic lock-in effect. These macroeconomic findings radically deconstruct human capital theory by asserting that developing nations must halt wasteful temporal personnel investments. Public policy must urgently shift toward integrated digital financial systems to secure local fiscal space stability against any future global economic recession threats.